Emerging trends in agri-nanotechnology fundamental and applied aspects - Singh, H. B., Dr; Mishra, Sandhya; Fraceto, Leonardo Fernandes; Lima, Renata de (CABI, 2018)
This book provides a thorough analysis of the progressive journey in agriculture from green revolution to nano revolution, with recommendations of certain key points to be addressed in current and future agri-nanotechnology research, on the basis of recognized knowledge gaps. It is hoped that the current volume will serve as a reference book for students, scientists, professors, teachers and researchers who are involved in the study and research on the various aspects of agri-nanotechnology.